Interpretation of The Phrase “Coercion” in The Compilation of Islamic Law as Reasons for Cancellation of Marriage - Neng Widya Millyuner; Adi Nur Rohman; Elfirda Ade Putri (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2021)
Marriage is a common thing in society with ubudiyyah elements in it. However, legal issues often accompany the sanctity of the marriage bond itself, such as the cancellation of a marriage due to an element of coercion from a third party. Article 71 Compilation of Islamic Law (KHI) states that one of the reasons for being able to apply for a marriage cancellation is because of coercion when the marriage took place. The purpose of this study is to analyze the meaning of the phrase